Poultry Disease Prevention and One Health Education - Rebecca, Tomasek (My University, 2020)
Poultry Disease Prevention Poultry exhibition requires pullorum disease testing, but many people don’t understand the significance of the disease or requirement. To address these concerns, this project aimed to better communicate what pullorum disease is and why it testing for it is important. An educational brochure was expanded as a guide to identify, report, and prevent disease in poultry. One Health Education One Health focuses on the interface of human, animal, and environmental health. This intersection is linked by many factors of disease, such as proximity and shared resources. Water scarcity is a driving force that pushes interactions between humans, livestock, and wildlife, increasing their close proximity and providing an opportunity for disease transmission. Additionally, approximately 75% of emerging diseases are zoonotic and maintained in a wildlife reservoir, but are transmitted to the human population when disease “spillover” occurs. Risk of disease to humans varies based on occupation, environmental conditions, increased interactions with wildlife, and more. One Health takes a transdisciplinary approach to address numerous factors of disease simultaneously to improve health. As a participant in a Rx One Health training course, I was able to experience and discuss multifactorial causes of disease, challenges to health, and ongoing projects in Tanzania. At the end of the course, my team developed a project proposal to assess antimicrobial resistance in poultry in Iringa Town, Tanzania. The goals of this project were to determine the extent of antimicrobial resistance and create a cost-benefit analysis to persuade poultry raisers to invest in management and facilities for their poultry operations.
Keywords: poultry; prevention; One Health